Strategies for the identification of ubiquitin ligase inhibitors. (19th January 2010) - Goldenberg, Seth J.; Marblestone, Jeffrey G.; Mattern, Michael R.; Nicholson, Benjamin
Abstract : Dysregulation of the UPS (ubiquitin–proteasome system) has been implicated in a wide range of pathologies including cancer, neurodegeneration and viral infection. Inhibiting the proteasome has been shown to be an effective therapeutic strategy in humans; however, toxicity with this target remains high. E3s (Ub–protein ligases) represent an alternative attractive therapeutic target in the UPS. In this paper, we will discuss current platforms that report on E3 ligase activity and can detect E3 inhibitors, and underline the advantages and disadvantages of each approach.